Effect of moisture on dental enamel in the interaction of two orthodontic bonding systems - de Magalhaes Bertoz, André Pinheiro [UNESP]; de Oliveira, Derly Tescaro Narcizo; Gimenez, Carla Maria Melleiro [UNESP]; Briso, André Luiz Fraga [UNESP]; Bertoz, Francisco Antonio [UNESP]; Santos, Eduardo César Almada [UNESP] (My University, 2013)
Objective: The purpose of this study was to assess by means of scanning electron microscopy (SEM) the remaining adhesive interface after debonding orthodontic attachments bonded to bovine teeth with the use of hydrophilic and hydrophobic primers under different dental substrate moisture conditions. Material and Methods: Twenty mandibular incisors were divided into four groups (n=5). In Group I, bracket bonding was performed with Transbond MIP hydrophilic primer and Transbond XT adhesive paste applied to moist substrate, and in Group II a bonding system comprising Transbond XT hydrophobic primer and adhesive paste was applied to moist substrate. Brackets were bonded to the specimens in Groups III and IV using the same adhesive systems, but on dry dental enamel. The images were qualitatively assessed by SEM. Results: The absence of moisture in etched enamel enabled better interaction between bonding materials and the adamantine structure. The hydrophobic primer achieved the worst micromechanical interlocking results when applied to a moist dental structure, whereas the hydrophilic system proved versatile, yielding acceptable results in moist conditions and excellent interaction in the absence of contamination. Conclusion: The authors assert that the best condition for the application of primers to dental enamel occurs in the absence of moisture. © 2013 Dental Press Journal of Orthodontics.
Keywords: Dental primer; Orthodontic brackets; Scanning electron microscopy